Environmental Sustainability Standards in Transport Alliances - Maren Wichmann; Wolfgang Kersten (Sustainability in Logistics and Supply Chain Management: New Designs and Strategies. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 21, 2015)
In 2012 about 23 percent of worldwide carbon dioxide emissions were caused by transportation. Therefore, it is desirable to improve the environmental sustainability of the transportation sector. In Germany a major part of road transportation is operated by small and medium sized enterprises (SME). They often lack the resources to identify and implement sustainability initiatives. However, to be able to compete with the big players SME tend to establish cooperations, so-called transport alliances. This paper presents an approach supporting the assessment and selection of sustainability measures within transport alliances. A literature review was conducted investigating measures to improve environmental sustainability as well as their environmental and economic impacts. Based on these findings focus group discussions and interviews were carried out in order to develop a concept that enables a company-specific selection of sets of measures. About 130 measures were identified and rated with respect to their environmental and economic capability. These findings were then used to develop a demonstrator program that supports both selecting measures and reporting the results.
10419/209190; https://econpapers.repec.org/RePEc:zbw:hiclpr:21
Keywords: 650; Transport; General Cargo Alliances; Sustainable Process Improvements; Environmental Sustainability